Pathway to copolymer collapse in dilute solution: uniform versus random distribution of comonomers - Dasmahapatra, Ashok Kumar; Nanavati, Hemant; Kumaraswamy, Guruswamy (Journal of Chemical Physics, 2007)
Monte Carlo simulations show that copolymers with uniformly (or periodically) distributed sticky comonomers collapse ``cooperatively,'' abruptly forming a compact intermediate comprising a monomer shell surrounding a core of the aggregated comonomers. In comparison, random copolymers collapse through a relatively less-compact intermediate comprising a comonomer core surrounded by a fluffy monomer shell that densifies over a wide temperature range. This difference between the collapse pathways for random and uniform copolymers persists to higher chain lengths, where uniform copolymers tend to form multiple comonomer cores. In this paper, we describe the formation of such an intermediate state, and the subsequent collapse, by recognizing that these arise from the expected balance between comonomer aggregation enthalpy and loop formation entropy dictated by the chain microstructure. (c) 2007 American Institute of Physics.